The Predicament of Ethnic Federal System - Yohannes Getahun (African Journal of Political Science)
The paper inquiries into ethnic federalism in lights of ethnic conflict and federal constitutional viability. It raises the basic question why some ethnic federations are successful in regulating ethnic relations while others are not. The history of federations has ample evidences that ethnic conflict, encompassing ethnic tensions and direct violence conflicts, causes and be caused by the failure of ethnic federalism. How a given ethnic federal system designed to adjust ethnic relations could self-contradictory induce far-reaching communal ethnic conflicts and ethnic based anti-regime activities is an interesting question. Answering that, the paper has given due consideration to the practices of defunct, fragile and mature ethnic federations and to the relevant conceptual and theoretical-back standings. The differences in the viabilities of these federations have shown the complicacy of ethnic federalism in meeting with the convulsive interplay between ethnic conflicts and federal system stability. In that regard, the paper finds seven factors: the democratic representativeness of federal structures, political parties, inclusive and overarching identities crossing ethnic lines, ethnic demographic shares, number of ethnic federal units and their ethnic composition, ethnic federal unit symmetry and geo-political setting. The concussion goes that ethnic federal design is not always an antidote for ethnic based claims and counter-claims. It rather could exacerbate the condition of ethnic politics, if it lacks those political, institutional and social ingredients inferred from the indicated factors.